Dampak Strategi Pelaksanaan Sistem Penjaminan Mutu Eksternal terhadap Kualitas Pendidikan di SMK Negeri Bansari - Nugroho, Priyo; Miyono, Noor (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
The importance of internal and External quality assurance system in education to improve the quality, relevance, and efficiency of management, as well as emphasizing that the implementation of ISO 9001 certification in SMK demands intensive preparation and continuous mindset change. The purpose of this study is to describe the implementation strategy of SPME in SMK Negeri Bansari and its impact. The research method used Descriptive method with qualitative approach aims to provide a systematic, factual, accurate description of the facts and characteristics of the object under investigation. This research was conducted for four months at SMK Negeri Bansari with three stages including the preparation stage, the implementation stage and the final stage of the research report. The results of this study are (1) the SPME implementation strategy by implementing three things, namely: forming a quality assurance team, carrying out the fulfillment of quality standards and carrying out evaluations. Through the implementation of the SPME implementation strategy starting in 2022, it has succeeded in maintaining accreditation and obtaining recognition from the community and ministries from programs and works; and (2) the impact of the SPME implementation strategy, namely positive impacts include improving the quality of education, improving the quality of process standards, recognition and high achievement, positive responses from the job market and commitment to renewal, negative impacts are challenges in maintaining quality, demands for continuous evaluation, difficulty in identifying deviations from renewal and continuous development, and pressure to continue to innovate.